Imprecatory Speech-Acts in the Book of Acts - Wenkel, David H. (The Asbury journal, 2008)
Theologies of prayer in Acts have long neglected imprecatory prayers or curses as integral to the theological agenda of Luke. This article seeks to survey the instances of imprecations in Acts to determine how they function as speech-acts. The article makes two conclusions about imprecations in Acts based on the survey. First, imprecations identify the true People of God in the midst of competing claims. Second, imprecations reveal how one can participate in the salvific work of God.